REVOLUSI ABOLISIONISME PADA NOVEL PERBUDAKAN UNCLE TOM’S CABIN KARYA HARRIET BEECHER STOWE - Amiruddin, Andy (Magistra Andalusia, 2019)
Literature and revolution cannot be separated from one another. On one hand, the revolution can create literary works from writers who are responsive to the changes that took place in their time. On the other hand, literary works can trigger the revolution in the people who read the work. In In Uncle Tom's Cabin, the relationship between literature and revolution can be seen in how the movement of the abolitionism group inspired Harriet Beecher Stowe to fight slavery through literary works. Harriet Beecher Stowe described slavery in South America and the abolitionist revolution against abolition of slavery.